Komunikasi Pemasaran Terpadu untuk Ekowisata Berbasis Komunitas di Bukit Tungkuwiri, Kabupaten Jayapura Provinsi Papua - Achmad Akbar Sanjaya Mulyadi; Rafel Makui (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study examines the effectiveness of integrated marketing communication in the development of community-based ecotourism at Bukit Tungkuwiri, Papua, with the aim of linking channel strategies and governance structures to socioeconomic impacts. A qualitative descriptive method was applied using purposive sampling involving visitors, managers, and local leaders. Data were collected through observation, semi-structured interviews, and documentation, and analyzed through reduction, presentation, and conclusion drawing using source and method triangulation. The results indicate that the orchestration of local government social media and printed materials expanded outreach and enhanced engagement, while community oral communication strengthened trust, identity, and educational experience. The appeal of the landscape, culinary and guide training, and local participation stimulated the economic turnover of stalls and small businesses, with tourist reach extending across provinces. The main constraints include dual authority systems, limited funding and human resources, and the absence of ticketing regulations and service SOPs. The discussion highlights the importance of cross-channel message consistency, brand architecture, and a monitoring–evaluation system linking digital metrics with on-site feedback. The study concludes that strengthening governance and local capacity is key to balancing promotion, conservation, and economic empowerment. The findings offer an operational model that can be replicated in similar rural destinations. Implications include establishing transparent ticket pricing, seasonal content calendars, curated experience packages, and cross-level collaboration among provincial, district, community, and business actors to ensure long-term sustainability.